Sterilization Treatment and Plantlet Regeneration of Guava (Psidium Guajava L. Vah. Beaumont) - Abdullah, Tajul Afif (2007)
This study was carried out to establish an efficient regeneration protocol for mass propagation of Psidium guajava L. var. Beaumont planting materials and as a system for recovery of transgenic plants in the improvement programme of the crop through genetic engineering. Aseptic study on grafted nodal explant of Psidium guajava L. var. Beaumont taken from the field was carried out to establish an efficient sterilization protocol. It was found that Treatment 5 was most efficient in producing the highest percentage of explant survival and the lowest percentage of bacterial and fungal contamination. In Treatment 5 nodal explants were soaked in 0.5% Benlate for 1 hour and placed under running tap water plus Tween 20 for 1 hour. Next. explants were placed in beaker and rinsed with 20% Clorox plus Tween 20 for 5 minutes before it were rinse with 0.05% AgN03 and 0.05% HgCl2 both for I -2 minutes. The explants were then washed with sterile distilled water (3 or 4 times) in order to remove the sterilizing agents used. Then the explants were soaked in liquid MS medium supplemented with 2 mglL BAP for overnight. Next morning, the ex plants were blotted dry before it were cultured on MS medium plus 1 mg/L BAP and 25 mg/L ascorbic acid. However, the percentage of phenolic browning of explant was high in this treatment. To reduce percentage of phenolic browning. it is suggested if Treatment 5 are added by dipping the explant into antioxidant solution (ascorbic acid 100 mg/L and citric acid 150 mg/L) before treating it with 50g/L Calcium hypochlorite (1 0-40 minutesand washed 5 times with sterile distilled water. It is also suggested for Treatment 5 that the explants are cultured onto media containing activated charcoal for a few days before it is transfer to MS medium + 1 mg/L BAP + 25 mg/L ascorbic acid.